Toward a homogenizing machine. (15th May 2020) - Dassonville, Thibault; Poncelet, Martin; Auffray, Nicolas
Abstract: The idea of an experimental homogenization device adapted to the case of architectural materials is discussed here. Although more advanced homogenization schemes exist, the case of average-field homogenization by KUBC within the framework of linear elasticity is studied here because of its (relative!) simplicity of adaptation to an experimental setup. The main idea here is to propose a device that is simple to implement, inexpensive but that allows to apply a load as close as possible to a perfect KUBC thanks to the use of pantographs to distribute the displacements on the edges of the specimen. For the purposes of the design and tests-design, a reduced model of the device has been developed.